Busulfan damages spermatogenic function by inducing orchitis. - Lingjun Zhao; Kaihui Wu; Shiyuan Xu; Songqi Liu; Kaimin Yuan; Dong Wang (PLoS ONE, 2025)
In order to clarify injure mechanism of busulfan to spermatogenic function, we treated mice with busulfan, the testicular and epididymal weights and sperm concentration significantly decreased and the sperm malformation rate increased over time. Moreover, testicular interstitial cell infiltration, a smaller seminiferous tubule, and disorganized and shed spermatogenic cells were also observed by immunohistochemical, immunofluorescence detection after the busulfan treatment. Furthermore, the enzyme-linked absorbance assays showed serum interleukin (IL)-6, IL-1β, and tumor necrosis factor-apha levels (inflammatory factors) were significantly upregulated; blood-testis barrier (BTB)-related protein levels (e.g., N-Cadherin, occludin, and connexin 43) and vimentine gradually decreased. So we infer busulfan treatment induced orchitis, further disrupted the BTB and disrupted the spermatogenic microenvironment, then decreased vimentine and gradually damaged the cytoskeleton, which cause spermatogenic cells losing their supporting from sertoli cells, androgen regulation was also affected, which was detrimental to spermatogenesis. The study result will improve the efficiency and safety in spermatogonial stem cell transplant recipients.